High-Level Production of Recombinant Snowdrop Lectin in Sugarcane and Energy Cane - Padilla, Carmen S.; Damaj, Mona B.; Yang, Zhong-Nan; Molina, Joe; Berquist, Brian R.; White, Earl L.; Solís-Gracia, Nora; Da Silva, Jorge; Mandadi, Kranthi K. (Frontiers in Bioengineering and Biotechnology, 2020)
Sugarcane and energy cane (Saccharum spp. hybrids) are ideal for plant-based production of recombinant proteins because their high resource-use efficiency, rapid growth and efficient photosynthesis enable extensive biomass production and protein accumulation at a cost-effective scale. Here, we aimed to develop these species as efficient platforms to produce recombinant Galanthus nivalis L. (snowdrop) agglutinin (GNA), a monocot-bulb mannose-specific lectin with potent antiviral, antifungal and antitumor activities. Initially, GNA levels of 0.04% and 0.3% total soluble protein (TSP) (0.3 and 3.8 mg kg–1 tissue) were recovered from the culms and leaves, respectively, of sugarcane lines expressing recombinant GNA under the control of the constitutive maize ubiquitin 1 (Ubi) promoter. Co-expression of recombinant GNA from stacked multiple promoters (pUbi and culm-regulated promoters from sugarcane dirigent5-1 and Sugarcane bacilliform virus) on separate expression vectors increased GNA yields up to 42.3-fold (1.8% TSP or 12.7 mg kg–1 tissue) and 7.7-fold (2.3% TSP or 29.3 mg kg–1 tissue) in sugarcane and energy cane lines, respectively. Moreover, inducing promoter activity in the leaves of GNA transgenic lines with stress-regulated hormones increased GNA accumulation to 2.7% TSP (37.2 mg kg–1 tissue). Purification by mannose-agarose affinity chromatography yielded a functional sugarcane recombinant GNA with binding substrate specificity similar to that of native snowdrop-bulb GNA, as shown by enzyme-linked lectin and mannose-binding inhibition assays. The size and molecular weight of recombinant GNA were identical to those of native GNA, as determined by size-exclusion chromatography and MALDI-TOF mass spectrometry. This work demonstrates the feasibility of producing recombinant GNA at high levels in Saccharum species, with the long-term goal of using it as a broad-spectrum antiviral carrier molecule for hemopurifiers and in related therapeutic applications.